Sociological Analysis Of Civilization Transformation - Aso Ibrahim Abdullah; Parwin Abubakir Mohammed Mohammed Amin (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
The cultural transformation is an important phenomenon in today’s current society. It is because of the sudden change that was caused by in all its systems. The results of natural and human factors have effects on the life of the individual itself and the community. According to society and theories presented, the presence of the educated elite is considered to be a necessity that has a major role in any type of transformation. This is due to their various different roles and the actual placed aspects of their social life. The concept of cultural transformation from the perspective of science changes. According to the types of societies, it has different expressions that are inspired by the reality of societies, global, cultural and historical changes that play major roles in its parts. This research includes a number of theories about civilization and cultural transformation from the perspective of intellectual and sociologists. It refers mostly to the intellectual and cultural construction of civilization, especially in its manifestations elements and conditions. This research showcasing the causes, effects, reflections of civilization altruism on the social environment, and the roles in the lives of the nation.